Diagnostic Accuracy of LDH in Detecting Birth Asphyxia: Cross sectional study - Muneeba Iftikhar, Iqra Ishtiaq, Aqsa Javaid, Husna Iram, Ayesha Hafeez, Maha Anwar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Among neonates, lack of oxygen results in multi-organ failure especially causing brain hypoxia resulting in hypoxic-ischemic encephalopathy (HIE). Aim: To determine diagnostic accuracy of LDH in detecting birth asphyxia keeping clinical signs of HIE as gold standard. Study Design: Cross-sectional study. Methodology: Neonates (n=180) fulfilling inclusion criteria were enrolled in this study from the Emergency Neonatal Unit and Neonatology Ward of Sir Ganga Ram Hospital, Lahore. Following informed consent, blood (1cc) was taken and LDH levels were measured. Antenatal scans determined gestational age. Chi-square test was applied with P-value <0.05 taken as significant. Results: Diagnostic accuracy of LDH for detection of perinatal asphyxia in term neonates had 90.20% sensitivity, 92.59% specificity and accuracy rate of 90.56%. Conclusion: It was concluded that the diagnostic accuracy of LDH is higher in detecting birth asphyxia keeping clinical signs of HIE as gold standard, and this test can be performed for evaluation of perinatal hypoxia. Keywords: Perinatal asphyxia, LDH and diagnostic accuracy.